Fact Sheet: The Cabrillo Port Liquefied Natural Gas (LNG) Project - Santa Barbara Environmental Defense Center:::::: (2006)
2 page document – Fact sheet that includes answers to: What is Liquified Natural Gas (LNG)?; What are the Problems with LNG?; Does California Have Better Alternatives; What is the Cabrillo Port LNG Terminal?; Should I be Concerned About the Cabrillo Port?